PENGARUH SISTEM PELAYANAN, KUALITAS PRODUK TERHADAP PENINGKATAN PENJUALAN DI RESTORAN CEPAT SAJI BURGER KING - ERISKA RINDIYANI ERISKA; Anita Kartika Sari; Lukman Nuzul Hakim (Lampung Selatan: Sekolah Tinggi Ilmu Ekonomi Muhammadiyah Kalianda, 2022)
The motivation behind this exploration is to figure out that of the MAP GROUP, namely Burger King Tunjungan Plaza 1 Surabaya, which is known as BK is probably the biggest establishment on the world. The examination strategy utilized isqualitative, which means using the condition of the object naturally. The focus of the researcher is then described according to the applicable rules. The objects in this study are how influential the service system and product quality are to sales at every operating hour of the restaurant open to closing, as well as a survey of consumers who are willing to provide an assessment through the official website with satisfactory results regarding product quality and service every time they visit Burger King Surabaya.